ANALYSIS OF THE BENEFITS AND RISKS OF USING SHARIA FINTECH IN SHARIA INVESTMENT - Fitri, Fitri (Journal of Islamic Economic Development, 2024)
This study examines the role of Sharia fintech in Sharia-based investments, offering ease of access, operational efficiency, and information transparency. The background of this research is the rapid development of Sharia fintech, which creates opportunities for digital-based investment without violating Sharia principles. The research employs a qualitative approach with literature studies to analyze the concepts, benefits, and risks of Sharia fintech usage. The findings reveal that Sharia fintech provides advantages such as portfolio diversification, ease of investment, and product innovation. However, it also poses risks, including technological, regulatory, and market uncertainty risks, which require effective risk management. This study concludes that Sharia fintech usage in Sharia investments provides modern financial solutions that align with Sharia principles while minimizing risks through proper management.